2020
DOI: 10.26434/chemrxiv.11972031.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resonance-Promoted Formic Acid Oxidation via Dynamic Electrocatalytic Modulation

Abstract: It is a truth universally acknowledged that faster catalysts enable the more efficient transformation of molecules to useful products and enhance the sustainable utilization of natural resources. However, the limit of <i>static</i> catalyst performance defined by the Sabatier principle has motivated a new approach to <i>dynamic</i> catalyst design, whereby catalysts oscillate with time between varying energetic states at sufficiently high resonant frequencies to overcome the Sabatier ‘… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This motivates repeated deposition-resting cycles to improve the efficiency of the Li-mediated process. Such a potential cycling approach has been used in the past to maintain stability of electrochemical systems [29]- [31], prevent electrocatalyst poisoning [32], or selectively promote specific reaction mechanisms [33]. Here, this concept is used to store and subsequently release high-energy electrons in order to continuously produce ammonia throughout the cyclic process.…”
Section: An Electrochemical Potential-cycling Strategymentioning
confidence: 99%
“…This motivates repeated deposition-resting cycles to improve the efficiency of the Li-mediated process. Such a potential cycling approach has been used in the past to maintain stability of electrochemical systems [29]- [31], prevent electrocatalyst poisoning [32], or selectively promote specific reaction mechanisms [33]. Here, this concept is used to store and subsequently release high-energy electrons in order to continuously produce ammonia throughout the cyclic process.…”
Section: An Electrochemical Potential-cycling Strategymentioning
confidence: 99%
“…In contrast, CO and halides (F 2 and Cl 2 ) are known to poison the catalyst surface (adsorption energy > -1.8 eV). [67][68] For reactions efficiently catalyzed on Pt (for example, HCOOH and NH 3 oxidation), 20 the substrates are chemisorbed (adsorption energy of ~ -0.6 eV for HCOOH, and ~ -1.0 eV for NH 3, see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…19 As such, the time-averaged catalytic activity can be enhanced above the Sabatier maximum as the catalytic system switches between rate-limiting steps, as demonstrated by a recent experimental work on the electro-oxidation of formic acid to carbon dioxide and hydrogen. 20 Recently, this potentiodynamic operation was utilized for selective enhancement of electrosynthesis of adiponitrile (main precursor to Nylon-66) by ~325% from acrylonitrile compared to potentiostatic operation, in favor of competing production of propionitrile 21 The adsorption energies of adsorbates need to uniquely vary for a dynamic system to provide enhanced reactivity under the same dynamic stimuli. [17][18] Materials design approaches that involve the optimization of catalyst composition have not yet been shown experimentally to assist with overcoming the Sabatier maximum, as the adsorption energies of key surface intermediates are typically bound to the same periodic linear scaling relationships.…”
mentioning
confidence: 99%
“…Indeed, Thomas and Thomas 12 provided extensive details on dynamic modelling during catalyst deactivation. Ertl 30 , Kobayashi [31][32][33][34] , Dauenhauer 35,36 , Carroll 37,38 and Boudart 39,40 studied reaction dynamics. Warshel [41][42][43][44][45] investigated the dynamic phenomena during enzyme catalysis and observed that the duration of the kinetics of catalytic transformation is much smaller than conformational dynamics.…”
Section: Introductionmentioning
confidence: 99%